IMF Credit: How Important Are Political Factors? A Robustness Analysis - Jan-Egbert Sturm; Helge Berger; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2002)
We test whether, in addition to economic conditions, IMF credit is influenced by political factors. On the basis of a panel model for 128 countries over the period 1972-1998, we find that debt service scaled to exports, international reserve holdings scaled to imports and economic growth, as well as investment are robustly related to IMF credit supply. Arguably, these results are broadly consistent with the IMF's mission. The only political variables which appear to be related to changes in IMF credit are government stability, the quality of the bureaucracy, and a dummy variable indicating the extent of political opposition. Possible interpretations of these findings are discussed.
Keywords: 330; IMF credit; political economy.